2011
DOI: 10.1590/s1807-59322011001100020
|View full text |Cite|
|
Sign up to set email alerts
|

An overview of recently published medical papers in Brazilian scientific journals

Abstract: A brief review intended as information to the readership of Clinics on papers recently published under various medical headings in Brazilian scientific journals recently indexed or about to be indexed in ISI-THOMSON Journal Citation Reports. Journals covered in this review are Acta Ortopédica Brasileira, Arquivos Brasileiros de Cardiologia, Jornal Brasileiro de Pneumologia, Revista Brasileira de Cirurgia Cardiovascular and Revista da Associação Médica Brasileira.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 79 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…In addition to religious uses, some of the species identified in this work are utilized for various purposes in Brazil. For example, Alves et al [ 11 ] and Dias et al [ 3 , 12 ] registered species of Cassis tuberosa and Eustrombus goliath being used by craftsmen for the production of pieces of art. In a bibliographic revision of animals used in traditional Brazilian medicine, Alves et al [ 14 ] and Alves and Dias [ 2 ] reported that C. tuberosa , Anomalocardia brasiliana and Crassostrea rhizophorae are utilized in the treatment of illnesses, including asthma, stomach aches, and osteoporosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to religious uses, some of the species identified in this work are utilized for various purposes in Brazil. For example, Alves et al [ 11 ] and Dias et al [ 3 , 12 ] registered species of Cassis tuberosa and Eustrombus goliath being used by craftsmen for the production of pieces of art. In a bibliographic revision of animals used in traditional Brazilian medicine, Alves et al [ 14 ] and Alves and Dias [ 2 ] reported that C. tuberosa , Anomalocardia brasiliana and Crassostrea rhizophorae are utilized in the treatment of illnesses, including asthma, stomach aches, and osteoporosis.…”
Section: Resultsmentioning
confidence: 99%
“…New studies that can verify about the use of these mollusks in other terreiros of Candomblés, acting in conjunction with populational and ecological studies, become necessary to determine the magnitude and impact on the species. With is worth to emphasize that the use and the commerce of this species for ornamental means is common in various cities of Brazil, not only utilized by the adepts of Candomblé [ 11 , 12 , 73 , 74 ].…”
Section: Magical-religious Decorationmentioning
confidence: 99%